Associate Professor Dr. Mohd Herwan Sulaiman: Innovator in Electrical Engineering and Artificial Intelligence - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 14 March 2025 – In the world of electrical engineering and artificial intelligence (AI), the name Associate Professor Dr. Mohd Herwan Sulaiman is increasingly recognised as an active researcher in power system optimisation and AI innovations in the energy sector. Hailing from Johor, he currently serves as the Deputy Dean (Research and Postgraduate Studies) at the Faculty of Electrical and Electronics Engineering Technology (FTKEE), Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).